Barriers and facilitators to shellfish cultivation. (28th January 2019) - Fox, Michaela; Service, Matt; Moore, Heather; Dean, Moira; Campbell, Katrina
Abstract: A literature review was conducted to determine the barriers and facilitators to shellfish cultivation using Northern Ireland (NI) as a case study. This review included 23 papers, published in 14 journals, indexed in the Web of Science database. The eligibility criteria included (i) peer‐reviewed articles or websites from key government or agency stakeholders in the aquaculture supply chain; (ii) had a primary focus on shellfish production; and (iii) made reference to the United Kingdom, Ireland or NI. Six key categories were identified as impacting the aquaculture sector: Economic, Environmental, Technical, Welfare, Political and Consumer factors. The most commonly cited codes within these categories included regulations, management decisions, environmental welfare, weather conditions, consumer needs and water quality. Within the scientific literature, the study designs were variable and NI‐specific data were limited. However, the recommendations were relatively consistent. More evidence‐based data collection is needed to better establish the status of the aquaculture industry in this region and to provide more effective management practices and recommendations. The information gained from this review allowed the identification and discussion of the challenges and opportunities for shellfish production worldwide; an insight into production in NI; and preliminary recommendations for improving this industry. As a result, the review offers important foundations and lessons for other aquaculture production units across the world to assess their industry.